THE MEANINGAND THE FUNCTIONING OF EQUALITY PRINCIPLE INBUSINESS COMPETITION SUPERVISORY COMMISSION DECISIONOFAGREEMENTPRICINGAPPROACH BASED ONMARKET STRUCTURE - Azizah Azizah (Saburai International Journal of Social Sciences and Development, 2017)
The interpretation and the application of the equilibrium principle in competition law raises issues of the philosophy of law, legal theory and legal dogmatic. Based on these issues, then the legal problems, namely: 1) What is the advantages and disadvantages of market structure approach used in the decision of the KPPU to analyze the principle of balance in competition law particularly in price fixing agreement. 2) How is the market structure approach in the KPPU decision, should be developed and used to analyze the principle of balance in competition law particularly in price fixing agreement. To answer the third issue, used the theory: (1) fairness, (2) equity markets, (3) the welfare state in the context of a market economy. This research is based on paradigmatic legal normative hermeneutic approach. The study concluded: 1) The advantages of the approach in the consideration of the legal market structure.KPPU decisions, creating more justice to the parties. The disadvantages of structural analysis approach, namely: the difficulty of proof in writing, setting procedural law clash between the KPPU and the Court of the country, lack of basic legal drafting guidelines that made by the KPPU. 2) In its development, the analysis approach used the Commission's market structure can be used as direct evidence in the form of a letter and stated in Government Regulation and prioritized approach to the analysis of market structure in the KPPU decisions on the prohibition of price fixing.